P111 Neurobiology of deception and moral cognition. Issue 3 (March 2017) - Karim, A.; Khalil, R.; Schneider, M.; Lotze, M.; Khedr, E.; Birbaumer, N.
Abstract : Question: Recent neuroimaging studies have suggested that the anterior prefrontal cortex (aPFC; BA 9/10) is involved in deception and moral cognition. However, since neuroimaging techniques only allow correlative statements, the functional contribution of the aPFC to deception and moral cognition remains elusive. Methods: In the first experiment we investigated, if modulating the excitability of the aPFC by transcranial direct current stimulation (tDCS) would alter deceptive behavior. Forty-four subjects participated in a thief role play, in which they were supposed to steal money and then to attend an interrogation with the Guilty Knowledge Test. In addition, the skin-conductance response (SCR) and the reaction time during verbal response (lie vs. truth) were measured. In a double-blind repeated measures design subjects received during the interrogation cathodal, anodal or sham tDCS. Furthermore, in order to measure skilful lying, we developed a lying quotient (LQ) relating the frequency of lies on critical questions to the frequency of lies on uncritical questions. In a second experiment we investigated, if modulating the excitability of the aPFC by transcranial direct current stimulation (tDCS) would alter moral judgments. Results: Remarkably, inhibition of the aPFC by cathodal tDCS did not lead to an impairment of deceptive behavior but rather to a significant improvement. This effect could be seen by faster reaction times in telling lies, but not in telling the truth, a decrease in sympathetic SCR and feeling of guilt while deceiving the interrogator compared to sham stimulation and a significantly higher LQ, which reflects skillful lying. Enhancing the excitability of the aPFC by anodal tDCS did not affect deceptive behavior, underpinning the specificity of the stimulation polarity. Moreover, in the second experiment we have shown that inhibition of the aPFC reduces moral conflict and reaction time while subjects are performing moral dilemma tasks. Conclusions: These findings give causal support to recent correlative data obtained by fMRI studies indicating a predominant role of BA 9/10 in deceptive behavior. Moreover, our findings suggest that inhibition of BA9/10 reduces the moral conflict during deception, presumably evoked by performing a self-perceived wrongful act.